
Use substitution method to and solve in terms of x using the first equation

Next, substitute it to the second equation

Then, substitute it back to first equation and solve for x

Now we have the following solutions

Get the square root of both x's and y's to get the solution
![\begin{gathered} x^2=-1 \\ √(x^2)=√(-1) \\ x=\pm i \\ x=i\text{ and }x=-i \\ \\ y^(2)=9 \\ √(y^2)=√(9) \\ y=\operatorname{\pm}3 \\ y=3\text{ and }y=-3 \end{gathered}]()
Getting the combination of ordered pairs we have the following solutions
